Creating a Practical Transdisciplinary Learning in Teaching Construction Entrepreneurship - Hansen, Seng; Rostiyanti, Susy F. (Journal of Engineering Education Transformations, 2025)
Construction Entrepreneurship is a unique subject taught in the Construction Engineering and Management program at the Universitas Agung Podomoro in Indonesia. As a new course, it is necessary to develop an effective and efficient teaching syllabus. This study describes construction entrepreneurship teaching through a transdisciplinary learning approach as an effective way to develop its syllabus. The transdisciplinary learning approach was chosen to provide insights into real-world problems to students through collaborative learning with industry speakers. Six construction entrepreneurs were invited to share their experiences in starting a construction business, followed by two reflective discussion forums to explore lessons learned from the sharing sessions. At the end of the term, online surveys were distributed to seek feedback from the enrolled students on the design, methods, and benefits of learning construction entrepreneurship. In addition, the survey was also intended to gather perspectives on the relevance and significance of this subject from construction students who had never taken it before. Overall, the approach to teaching construction entrepreneurship to enrolled students was found to be effective. The statistics also reveal the high interest of students from other construction-related programs in taking this subject.